Analisis E-Service Bursa Kerja Online (Studi Kasus pada E-Makaryo Dinas Tenaga Kerja dan Transmigrasi Provinsi Jawa Tengah) - Wulandari, Kiki; Hariani, Dyah; Sulandari, Susi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
E-Makaryo is a public service run by the Manpower and Transmigration Department of Central Java which aims to reduce unemployment in Central Java. The purpose of the study was to find out the implementation of the online job fair E-Service (EMakaryo) of the Manpower and Transmigration Department of Central Java and to know the supporting and inhibiting factors. The method of this research is descriptive qualitative. The data collection techniques of this research are observation, interviews, and documentation. The theory used is is E-Service according to the Journal of Andi Muh Fikram et al, reflects 3 main components in E-Service, namely service providers, service recipients and service channels. The results of the study show that E-Service in E-Makaryo is not achieved optimally in terms of the service provider aspect which is still lack of officers so that they are not able to provide the best service to the society. Other aspects, such as service users, lack of encouragement to attract the public, such as socialization that has not been held and service channels still have obstacles in the convenience of use, considering the network sometimes has errors The driving factor is the attitude of leadership to employees, employees are rewarded for the tasks that have been achieved and the convenience in the form of services that can be accessed anywhere, while the inhibiting factor is the lack of human resources in E-Makaryo services and network weaknesses in each region make the inhibiting factors for online services . Based on these problems, the researcher suggests that the implementation of socialization must touch several targets.